3D hybrid-domain full waveform inversion on GPU. (October 2015) - Liu, Lu; Ding, Renwei; Liu, Hongwei; Liu, Hong
Abstract: The traditional frequency-domain full waveform inversion (FWI) method has limited application for 3D case due to its significant computational challenges and huge memory cost. The time-frequency hybrid-domain FWI is thus utilized to combine the computational efficiency of time-domain FWI and multi-scale inversion of frequency-domain FWI. We present a simplified hybrid-domain FWI method. Compared with the previous hybrid-domain FWI, our method can take one less Discrete Fourier Transform (DFT) and one less inverse Discrete Fourier Transform (IDFT) for single iteration and achieved the equivalent inversion effect. Meanwhile, the hybrid-domain FWI is very suitable for fine-grained parallel computation, and the application of graphic processing unit (GPU) has significantly enhanced the computation efficiency. Modeling, boundary absorption and DFT are the most time-consuming modules. The occupancy of the three kernels achieved a good level as Compute Unified Device Architecture (CUDA) Visual Profile shows and the bandwidth usage has been much improved by introducing the tiling method for 3D finite difference problem. Finally, our hybrid-domain FWI is applied to a 3D model on our personal computer equipped with GTX 680 graphic card, and complexity analysis of our algorithm is presented. The results further confirm the feasibility of this technique. Highlights: We simplified the flow of the previous hybrid-domain FWI method. Our method achieves equivalent effect with previous one using simplified flow. GPU is used here to enhance the efficiency of our method.